ItaSaúde : desenvolvimento de um aplicativo móvel para a organização e mediação de informações sobre serviços públicos de saúde no município de Itabaiana - Oliveira, Camila de Jesus (2021)
This work deals with the development of a mobile application for the organization and dissemination of information about public health services in the municipality of Itabaiana, Sergipe. It is, therefore, a technological development research, aimed at the use of information systems to promote access to information about public services. As part of its social impact, it is estimated that the dissemination of information about health services and, more specifically, about the services that are offered in Basic Health Units and Specialized Centers, organized according to the contexts of use, has educational potential on the decisions of users of the health system, contributing to the optimization of the use of network services and to the reduction of queues at the Regional Hospital. The production of the mobile application took place in five stages, according to the User-Centered Design approach: 1) Data collection; 2) Modeling; 3) Navigation project; 4) Abstract interface design; 5) Development. These phases were supported by the literature review on the Access to Information Law; accountability; usability, organization and dissemination of information and information architecture. In turn, data on public health services available in the municipality of Itabaiana were collected through document analysis, including the analysis and systematization of the content present on the official websites of the city, state and federal government, as well as the National Registry of Unified Health System Health Establishments.